Intestinal parasitic infection of immunocompromised children with diarrhoea: clinical profile and therapeutic response - Nikmah Salamia Idris; Pramita Gayatri Dwipoerwantoro; Agnes Kurniawan; Mardjanis Said (Journal of Infection in Developing Countries)
Background: Parasitic gastrointestinal infections have been variably reported among immunocompromised adults while data on children have been limited. This prospective cross-sectional study aimed to assess the clinical profile of intestinal parasitic infections among immunocompromised children with diarrhoea and their treatment response.